Hypothyroidism & Homoeopathy – A Case Study (Advancements in Homeopathic Research, 2022)
Thyroid disorders are very commonly seen in patients across the globe amongst which hypothyroidism stands out as the commonest. Thyroid hormones have a noteworthy control over numerous vital elements of the human body and along these lines have a critical job in looking after homeostasis. Therefore, the hypothyroid state is related to a wide range of indications influencing practically all physiological capacities. Among the significant organs affected, the nervous system and body metabolism are extremely influenced. Facial appearance, including visual changes, is peculiar for the hypothyroid state. The most unmistakable visual characteristic features of hypothyroidism incorporate loss of eyelashes and eyebrows, particularly on the temporal side, puffiness of the eyelids, protrusion and irritation of eyes. Drooping of the eyelids is likewise found in a few patients because of loss of sympathetic tone.1
Keywords: Thyroid Disorder; Hypothyroidism; Homoeopathy; Case report; Thyroid Hormone